ECO HIVE: Implementasi Konsep Arsitektur Hijau di Youth Public Space dengan Pendekatan Iklim - Amanda, Jasmine Putri; Fachrudin , Hilma Tamiami (Universitas Medan Area, 2025)
Medan City has an urgency for public spaces that are not only functional but also sustainable. This research aims to design a Youth Public Space by applying the principles of Green Architecture through the working with climate approach. The research methods used include literature study, field observation, user questionnaire, and SWOT analysis of the selected site on Dr. Mansyur Street, Medan City. The analysis focused on space requirements, local climate conditions, site potential, and the application of sustainable features such as rainwater conservation, optimization of cross ventilation, and the use of secondary skin for energy efficiency. The results of the analysis show that the use of hexagonal shapes in the plan can improve air circulation and natural lighting, while the southward orientation of the building and the rainwater harvesting system effectively support resource conservation. The design concept also involves a participatory approach, taking into account the preferences and needs of local youth. In conclusion, the designed Youth Public Space not only serves as a platform for social, creative, and educational activities, but also as a representation of Medan City's commitment to sustainable development, hoping to encourage innovation, collaboration, and environmental awareness among the younger generation.